Knowledge-action systems for seasonal to interannual climate forecasting : summary of a workshop - Cash, David W.; Buizer, James (National Academies Press, 2005)
"The workshop featured in this report, Decision Support Systems for Seasonal to Interannual Climate Forecasting, was held May 6-8, 2004. It served to provide an examination of lessons learned about the design of effective systems for linking knowledge to action based on experience from the specific case of decision support systems for seasonal to interannual climate forecasting. The area of seasonal to interannual climate forecasting was chosen because: (1) climate variability has significant impact on decision making for sustainability; (2) there have been important advances in the science of climate forecasting in the last two decades; and (3) there is active experimentation underway in that area, involving various institutional approaches to producing and using climate forecasts. Lessons for institutional design may also be easier to draw in the area of seasonal to interannual climate forecasting compared to others because it is a relatively new field--young enough to include some systems that were designed 'from scratch' as knowledge-action systems--but still includes the more typical incremental systems. In addition, the nature of seasonal to interannual climate forecasting, which involves complex, rapidly changing, interdisciplinary science at scales ranging from local, to regional, national, and supranational, makes it particularly relevant to other areas of sustainability science, which often involve similar complexities"--Page x.